Exercise-related mental health problems and solutions during the COVID-19 Pandemic - Morrey, L. B.; Roberts, W. O.; Wichser, L. (Current Sports Medicine Reports, 2020)
Most people will find it challenging to maintain their men-tal health during the COVID-19 pandemic. People with a his-tory of mental illness, including anxiety disorders, mooddisorders, posttraumatic stress disorder (PTSD), and relateddisorders are now forced to navigate the fear and trauma ofliving through a pandemic, often in isolation. Even individualswith no history of anxiety, depression, or PTSD may experi-ence a level of stress during the pandemic that makes it diffi-cult to maintain their mental health. Exercise is a controlmechanism for many living with mental illness and a protec-tive factor in the lives of those without mental illness. Mentalhealth and physical health are closely intertwined when itcomes to exercise. However, exercise routines are heavilydisrupted by this pandemic. Our focus is to highlight howthe disruption in individual exercise programs requires dis-tinctive solutions to protect and enhance mental health duringthe COVID-19 pandemic using a case-based approach